Network pharmacology and in vivo experiment-based strategy to investigate mechanisms of JingFangFuZiLiZhong formula for ulcerative colitis. (31st December 2022) - Wang, Mengyuan; Li, Jianan; Yin, Yuzhang; Liu, Liying; Wang, Yifei; Qu, Ying; Hong, Yanqiu; Ji, Shuangshuang; Zhang, Tao; Wang, Nan; Liu, Jinlong; Cao, Xu; et al.
Abstract: Background: Ulcerative colitis (UC), a chronic inflammatory disease, often cause carcinogenesis, disability, and intestinal perforation. The JingFangFuZiLiZhong formula (JFFZLZ) shows a good effect against UC in the clinic. Hence, we aim to investigate the mechanisms between JFFZLZ and UC via network pharmacology data mining and in vivo experiments. Methods: We obtained active constituents and related targets from public databases. The overlapped genes between JFFZLZ and UC targets were further analysed by enrichment analysis. The active constituents and hub targets were used to construct molecule docking analysis. We finally screened out nine hub targets and their expressions were verified in the Gene Expression Omnibus database and UC rats' colon tissues after JFFZLZ treatment. Results: The results implied that JFFZLZ mainly regulated signal transduction, metabolites production, and inflammation pathways. The expression of STAT3, CXCL8, IL6, CXCL12, TNF, TP53, and PTPN11 were both upregulated in colon tissues of UC patients and UC rats. While RELA, EGFR, and TP53 were downregulated in UC patients, but upregulated in UC rats. Furthermore, JFFZLZ could repair UC rats' colon mucosal damage and promote the healing of ulcers via regulating the hub targets. Conclusion: These results elucidated that the anti-UC effect of JFFZLZ was closely related to the inhibition of inflammatory response, inhibition of oxidative stress, and repairing colon mucosal damage through different signal pathways. The findings could contribute to a better understanding of the regulation mechanisms in JFFZLZ against UC. Key messages: JFFZLZ could reduce the inflammatory infiltration and repair UC rats' colon mucosal damage. Through the network pharmacology-based strategy and public database mining, we obtained the hub targets and key pathways between JFFZLF and UC. The mechanism of JFFZLZ against UC was inhibition of inflammatory response and oxidative stress by regulating the expression of the hub targets.